Archaeological Investigations: Salt River Project Palo Verde to Kyrene 500 kV Transmission Line Right-of-Way, Private, State and Bureau of Land Management (Phoenix District Office) Lands, Maricopa, Arizona: Final Report for an Archaeological Survey of the Palo Verde to Kyrene 500 kV Transmission Line, Maricopa, County, Arizona - Powers, Margaret A.; Keane, Mark J.; Weaver, Donald E. (Museum of Northern Arizona, Department of Anthropology, 1978)
At the request of Salt River Project, the Museum of Northern Arizona conducted an archaeological survey of a proposed 500kV transmission line between the Palo Verde Nuclear Generating Station (near Wintersburg, Arizona) and the Kyrene Substation (near Tempe, Arizona). During survey of the 73.3 mi right-of-way, evidences of historic and prehistoric activity were recorded at 10 sites and 43 loci of isolated artifacts or features. With few exceptions, all identified remains could be assigned to the Hohokam culture. The Museum recommends, where feasible, that all cultural remains be avoided. In instances where sites or portions of sites cannot be avoided specific mitigation recommendations are presented. This file includes related correspondence.